Hubungan Infeksi Torch Pada Kehamilan Dengan Kejadian Kelainan Kongenital Pada Bayi Baru Lahir - Zida Maulina Aini; Juminten Saimin (Halu Oleo University, 2017)
ABSTRACT Introduction: TORCH infection in pregnancy in Indonesia shows a high prevalence, ranging from 5.5% to 84%. The results showed that from 100 samples of pregnant women who had an infection, one of TORCH was found to have 12% of children with congenital abnormalities, 70% had abortion and 18% had Intra Uterine Fetal Death (IUFD). TORCH infection has not received serious attention in pregnant women in Southeast Sulawesi. Methods: The design of this study used cross-sectional studies. The research was conducted in RS Ibu and Anak Permata Bunda and RS dr.Ismoyo Kendari from 2013-2016. Sample examination of TORCH infection include IgG Toxoplasma, IgG Rubella, and IgG Cytomegalovirus. The results of the examination are TORCH infection (IgG Toxo, IgG Rubella, IgG CMV) and observation of pregnant mother until newborn. Bivariate analysis was done to see the relationship between independent variable and dependent using statistical test odds ratio (OR) 2x2 contigency table with 95% confidence level (α = 0,05). Result: Subjects of this research were 33 people by total technique Sampling. Results examination of TORCH infection are obtained: IgG Toxoplasma (+), IgG Rubella (+), IgG CMV (+), IgG Toxoplasma (+) IgG Rubella (+), IgG Toxoplasma (+) IgG CMV (+), IgG Rubella (+) IgG CMV (+), and IgG Toxoplasma (+) IgG Rubella (+) IgG CMV (+). The most frequent result of TORCH infection was IgG Toxoplasma (+) IgG Rubella (+) IgG CMV (+) of 11 samples (33.3%). Based on the obeservation of pregnant women to childbirth, there were 12 samples (36,4%), Abortus 8 samples (24,2%), congenital abnormalities 7 samples (21,2%), Intra Uterine Fetal Death (IUFD) 4 samples (12.1%), and Blighted Ovum (BO) of 2 samples (12.1%). Based on result of data analysis with Chi-Square statistical test to correlation of TORCH infection with congenital incidence in newborn p value was 0,092 (p> 0,05). These results suggest that TORCH infection is not associated with the incidence of congenital abnormalities in newborns. Conclusion: Based on this research, it was found that there was no correlation between TORCH infection in pregnancy with incidence of congenital abnormality (P = 0,092, p> 0,05). Some of the high yields of TORCH IgG titers have a baby aterm output. While the value of IgG titer that is not too high have abortus output, IUFD and congenital abnormalities. Keyword: TORCH, IgG, Congenital Disorders